Doodle illustration: shark endangerment awareness campaign / Izzat Amir Hamdan - Hamdan, Izzat Amir (Faculty of Art and Design, 2020)
Shark are the most fearsome creatures in the ocean world but do people know that sharks are the one that is being hunted? It is said that sharks fin soup contains beneficial substances.